2022
DOI: 10.1177/15234223221135557
|View full text |Cite
|
Sign up to set email alerts
|

Hair Bias in the Workplace: A Critical Human Resource Development Perspective

Abstract: The Problem Managers and other individuals in the workplace may have a bias, either conscious or unconscious, against Black women based on their appearance. Since slavery, Black people with lighter skin complexion and straighter hair have been given preferences and privileges not afforded Black people with darker skin or those with naturally kinky hair. This study brings this subtle form of discrimination to the attention of Human Resource Development professionals and sheds light on how such interactions may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The exception was Hutchins and Kovach (2019) which reviewed each institution’s grant proposal and website. The other half ( n = 12) were non-empirical studies, including perspective (Byrd, 2014; Davis et al, 2020; Johnson & Thomas, 2012; Lanier et al, 2022; Trusty et al, 2023), conceptual (Kang et al, 2015; Santamaría et al, 2022; Thomas et al, 2010), and literature review studies (Alfred et al, 2019; Manongsong & Ghosh, 2021; Sims, 2022; Syed & Ali, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The exception was Hutchins and Kovach (2019) which reviewed each institution’s grant proposal and website. The other half ( n = 12) were non-empirical studies, including perspective (Byrd, 2014; Davis et al, 2020; Johnson & Thomas, 2012; Lanier et al, 2022; Trusty et al, 2023), conceptual (Kang et al, 2015; Santamaría et al, 2022; Thomas et al, 2010), and literature review studies (Alfred et al, 2019; Manongsong & Ghosh, 2021; Sims, 2022; Syed & Ali, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In the third issue of ADHR 2022, the editors (Sims & Carter, 2022) again highlighted the problem of the lack of leadership research on women of color in HRD since the call to action in the 2009 Special Issue of ADHR. Four research articles (Lanier et al, 2022; Santamaría et al, 2022; Sims, 2022; Trusty et al, 2023) responded to their call. Specifically, Sims’s (2022) literature review of women of color leaders in the HRD journals showed that they are still not represented in leadership even after the 2009 Special Issue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Black girls' pubertal development and skin color have been associated with greater monitoring and punishment in school settings, where Black girls receive harsher punishment than their White peers (Blake et al, 2022;Morris, 2016;Osinubi et al, 2022). Similarly, American cultural spaces still enforce European hair standards on Black women in work and educational spaces, despite evidence of these practices' real potential for psychological and physical harm (e.g., Dawson et al, 2019;Essien & Wood, 2021;Trusty et al, 2023). In turn, Black women who do not embrace or present White standards of beauty not only face negative evaluations of their appearance but also are evaluated more negatively across personality, intelligence, employment options, economic mobility, and educational domains (e.g., Dawson et al, 2019;Essien & Wood, 2021;Harrison & Thomas, 2009;Trusty et al, 2023;Wade & Bielitz, 2005).…”
Section: History Of Body Image Among Black Women In Psychological Res...mentioning
confidence: 99%
“…Similarly, American cultural spaces still enforce European hair standards on Black women in work and educational spaces, despite evidence of these practices’ real potential for psychological and physical harm (e.g., Dawson et al, 2019; Essien & Wood, 2021; Trusty et al, 2023). In turn, Black women who do not embrace or present White standards of beauty not only face negative evaluations of their appearance but also are evaluated more negatively across personality, intelligence, employment options, economic mobility, and educational domains (e.g., Dawson et al, 2019; Essien & Wood, 2021; Harrison & Thomas, 2009; Trusty et al, 2023; Wade & Bielitz, 2005). Further, these messages surrounding beauty standards not only impact evaluations of specific phenotypic cues but also influence the physical, emotional, and psychological well-being of Black women across their lifespan (e.g., Abrams et al, 2020; Bartholomew et al, 2023; Landor & McNeil Smith, 2019).…”
Section: History Of Body Image Among Black Women In Psychological Res...mentioning
confidence: 99%